1998
DOI: 10.1016/s0928-8244(98)00063-7
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular organisation of recombinant Yersinia pestis F1 antigen and the effect of structure on immunogenicity

Abstract: Yersinia pestis, the causative organism of plague, produces a capsular protein (fraction 1 or F1 antigen) that is one of the major virulence factors of the bacterium. We report here the production, structural and immunological characterisation of a recombinant F1 antigen (rF1). The rF1 was purified by ammonium sulfate fractionation followed by FPLC Superose gel filtration chromatography. Using FPLC gel filtration chromatography and capillary electrophoresis, we have demonstrated that rF1 antigen exists as a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 18 publications
5
48
1
Order By: Relevance
“…These results are consistent with previous observations that a combination or fusion of these Ags has an additive protective effect when used to immunized mice against plague (12,(31)(32)(33). The F1-Ag and V-Ag are considered the most effective candidates for vaccines against plague, and vaccination with each protein alone is sufficient for protecting mice against both bubonic and pneumonic plague (16,20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous observations that a combination or fusion of these Ags has an additive protective effect when used to immunized mice against plague (12,(31)(32)(33). The F1-Ag and V-Ag are considered the most effective candidates for vaccines against plague, and vaccination with each protein alone is sufficient for protecting mice against both bubonic and pneumonic plague (16,20).…”
Section: Discussionsupporting
confidence: 92%
“…To enable development of a subunit vaccine to plague, efforts have focused on two primary Y. pestis antigens (Ags), the outer capsule protein antigen (F1-Ag), which is believed to help avoid phagocytosis (3,35), and the low calcium response (LcrV) protein or V-Ag, which has been suggested to mediate a suppressive effect upon Th1 cells via the stimulation of interleukin-10 (IL-10) (28). When given in combination, these vaccines effectively protect against bubonic and pneumonic plague (16,20). While the observed protective immunity is largely antibody (Ab) dependent, Y. pestis is an intracellular pathogen, and new data have shown that cellular immunity can contribute to protection against plague (23,24,27).…”
mentioning
confidence: 99%
“…We further aimed to address any uncertainty as to the comparative level of plague protection achievable using monomeric versus multimeric F1-V preparations. Concerns regarding monomeric F1-V plague vaccine efficacy are based upon prior haptan reports, where monodisperse antigens induced weaker immune responses than did protein assemblies [10], and the disease context in which F1 subunits are encountered as multimeric fiber structures [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Protein subunit vaccines can overcome many of these problems, and recombinant forms, produced in a nonpathogenic strain, lead to a large reduction in costs. Vaccination with recombinant Caf1 (rCaf1) (20,35) alone or in combination with other Y. pestis proteins (37) confers protection against plague in mice (35). Sera from humans recovering from plague contain significant titers of anti-Caf1 antibodies (27), and the efficacy of vaccination with Caf1 in humans is being evaluated (38).…”
mentioning
confidence: 99%
“…CU polymers are composed of small immunoglobulin-like subunits linked by a "donor strand complementation" mechanism, in which a ␤-strand is donated by the next molecule in the chain to create polymers of stable monomers joined by noncovalent links (32). Naturally occurring CU proteins generate defined structures (8,25), whereas recombinant CU proteins form either aggregated structures (20) or vaccine-chaperone dimers (18) or are unstable (14). Future development of protein therapeutics is being driven toward easily assayed final products that are not defined simply by the manufacturing process (5), and one important step is the design of new regulatory-friendly protein therapeutics.…”
mentioning
confidence: 99%